2003
DOI: 10.1051/agro:2002081
|View full text |Cite
|
Sign up to set email alerts
|

Simulating water uptake in the root zone with a microscopic-scale model of root extraction

Abstract: Root water uptake is a key element for analysing the evolution of soil water content, which regulates crop transpiration. Our objective was to design a model taking into account the vertical water redistribution and the root water uptake in order to assess the regulation of plant transpiration induced by the effective soil water availability. To do so, the root water uptake is described with a microscopic-scale model integrated within a classical model of vertical water redistribution. For root water uptake, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
2
20
0
1
Order By: Relevance
“…Similarly, the gradient of ψ around roots is small in the case of soils with large K(θ), such as potting composts, sand or vermiculite (Jones and Tardieu 1998;Personne et al 2003). Moreover, similarly to this study, Carminati et al (2010) recently found no gradients of water content in the lupin-sandy soil rhizosphere after a drying period (but an increase of θ towards the roots after soil rewetting), water content distributions being recorded by non-destructive neutron radiography.…”
Section: Rhizosphere Hydrodynamicssupporting
confidence: 77%
“…Similarly, the gradient of ψ around roots is small in the case of soils with large K(θ), such as potting composts, sand or vermiculite (Jones and Tardieu 1998;Personne et al 2003). Moreover, similarly to this study, Carminati et al (2010) recently found no gradients of water content in the lupin-sandy soil rhizosphere after a drying period (but an increase of θ towards the roots after soil rewetting), water content distributions being recorded by non-destructive neutron radiography.…”
Section: Rhizosphere Hydrodynamicssupporting
confidence: 77%
“…The latter corresponds to previous approaches to modelling HR (e.g. Amenu and Kumar, 2007;Personne et al, 2003), while modelling drought-avoiding roots in a hydrological model has not been done before to our knowledge. The better reproduction of observations by the optimisation-based model suggests that drought-avoiding roots dominate in the investigated savanna, but it does not allow conclusions about the generality of such a strategy.…”
Section: Hydraulic Redistributionsupporting
confidence: 53%
“…The latter has recently been modelled (Laio, 2006) using a stochastic approach to describe the water balance of a horizontal soil layer of infinitesimal thickness (e.g., Lai and Katul, 2000) in the presence of a vertical density distribution of roots and relating root uptake to evapotranspiration rate. The latter choice for water and nutrients uptake by roots is in accordance with some of the most common uptake models existing in literature (e.g., Feddes et al, 2001;Sperry et al, 2002), although more detailed approaches are available (Itoh and Barber, 1983;Personne et al, 2003;Roose and Fowler, 2004). On that basis a first step towards describing the root and soil moisture inter-adjustments (i.e., hydrotropism) has been proposed by Schenk (2005) and Laio (2006).…”
Section: Root Development In Relation To Soil Moisture and Nutrient Dmentioning
confidence: 67%
“…More recently, the active role of vegetation has been considered (e.g. see Gurnell and Petts, 2002;Gurnell et at, 2001;Steiger et al, 2003;Perona et al, 2008Perona et al, , 2009b) and coupled to the equations of morphodynamics in order to better explain the role that riparian vegetation play when colonizing point bars (Perucca et al, 2007) as well as the reciprocal interactions with river hydrology as a Markov process with dichotomic noise at both the transect and corridor scales (Perona et al, 2009a;Muneepeerakul et al, 2007). Gran and Paola (2001) used Alfalfa grass to study the effect of vegetation on a braided stream under steady flow conditions.…”
Section: River Morphodynamics and Vegetation Interactionsmentioning
confidence: 99%